2020
DOI: 10.1371/journal.pone.0240550
|View full text |Cite
|
Sign up to set email alerts
|

Viremia copy-years and risk of estimated glomerular filtration rate reduction in adults living with perinatal HIV infection

Abstract: Among people with perinatal HIV infection (PHIV), non-communicable diseases, such as chronic kidney disease, are increasing. Both HIV replication and antiretroviral therapy are recognised causes of renal impairment. Objective of the study is to describe the impact of viremia copy-years (VCY) and antiretroviral therapy on trend of estimated glomerular filtration rate (eGFR) in a cohort of adults with perinatal HIV infection. We conducted a multicentre observational study in sixty adults living with PHIV across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the modern ART era, with life expectancy extended approximately 20 years since 2000 among PWH with access to care [ 2 ], it is critical to ascertain HIV care metrics not only predictive of death but also of aging-related NACM development. Recent analyses have demonstrated that cumulative HIV-1 viremia is associated with incident myocardial infarction [ 18 , 24 ], hypertension [ 25 ], renal insufficiency [ 26 , 27 ], and non-AIDS cancer [ 28 ]. Our study uniquely adds to this growing body of literature by assessing multimorbidity as a composite outcome and by focusing on women, a group traditionally underrepresented in HIV research although uniquely at risk of NACM [ 5 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the modern ART era, with life expectancy extended approximately 20 years since 2000 among PWH with access to care [ 2 ], it is critical to ascertain HIV care metrics not only predictive of death but also of aging-related NACM development. Recent analyses have demonstrated that cumulative HIV-1 viremia is associated with incident myocardial infarction [ 18 , 24 ], hypertension [ 25 ], renal insufficiency [ 26 , 27 ], and non-AIDS cancer [ 28 ]. Our study uniquely adds to this growing body of literature by assessing multimorbidity as a composite outcome and by focusing on women, a group traditionally underrepresented in HIV research although uniquely at risk of NACM [ 5 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measures of cumulative HIV-1 viremia have been associated with mortality among ART-treated PWH [ 18 , 19 , 20 , 21 , 22 ] (even independent of CD4 count) [ 23 ], and with individual NACM including myocardial infarction [ 18 , 24 ], hypertension [ 25 ], renal insufficiency [ 26 , 27 ], and non-acquired immune deficiency syndrome (AIDS) cancer [ 28 ]. However, previous studies evaluating cumulative HIV-1 viremia as a prognosticator of non-AIDS mortality and morbidity have comprised male-predominant cohorts and have not assessed the effect of virologic nonsuppression on aging-related multimorbidity.…”
mentioning
confidence: 99%
“…In this context, viremia copy years (VCY), a metric of cumulative HIV RNA burden calculated based on longitudinal viral load data, has been used to summarize in a single value the viral burden of years ( 35 , 36 ). VCY is considered a reliable marker of past viral burden and has been associated with mortality and organ damage in people living with HIV and PHIV ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%